A Critical Discourse Analysis of the Representation of the Iranian Protests in Selected Newspapers - Atheer Dakhil Shati; Enas Naji Kadhim (Ph.D.) (Journal of College of Education, 2024)
The present study is devoted to the analysis of the representation of the Iranian protest in selected newspapers. The protests in Iran are regarded a turning point in the history of the Islamic Republic of Iran. The protests are of interest to many national and international newspapers who took the events into serious consideration. The study aims at investigating these events from the CDA point of view. It, however intends to uncover the linguistic components, the ideologies and the power relations that are employed in the selected reports. The study is qualitative in nature and is based on Fairclough’s (2001) three-dimensional approach. Two reports from two newspapers; the Washington Post and the Tehran Times, are selected as samples of the current study. After analysing the selected data, it has been found that the two newspapers contain different linguistic features such as overwording, lexical relations, besides that they encompass several ideologies and the representation of various power relations. These linguistic and non-linguistic strategies are utilised by the editors when addressing the Iranian protests. The American newspaper is assured to positively represent the protest and support them, while the Iranian newspaper is proved to negatively describe the protests and deny the protestors’ rights in expressing their opinions and demands.
Keywords: Iranian Protests, CDA, Ideologies, Strategies, Newspapers.